Kinetic and Mechanistic Study of Oxidation of Chalcones by Morpholinium Chlorochromate with Oxalic Acid as Catalyst - K. Rajalakshmi (Challenges and Advances in Chemical Science Vol. 8, 2022)
The kinetics of oxidation of chalcones by morpholinium chlorochromate (MCC) has been studied in 55% acetic acid-water (v/v) medium. The reactions carried out under pseudo-first-order conditions by maintaining always the substrate concentration in excess over that of MCC. The reaction showed unit order dependence each with respect to oxidant and catalyst and fractional order with respect to substrate and H+ ion. Increased ionic strength has no effect on the reaction rate. In the case of substituted chalcones, the order with respect to substrate varies depending upon the nature of the substituent present in the ring. In general, the electron withdrawing substituents retard the reaction rate while the electron releasing substituents enhance the rate of the reaction. From the kinetic data obtained, the activation parameters have been calculated and a suitable mechanism has been proposed.